Devs Modeling of Large Scale Web Search Engines - Inostrosa-Psijas, A (Institute of Electrical and Electronics Engineers Inc., 2015)
Modeling large scale Web Search Engines (WSEs) is a complex task. It involves many issues such as representing user s behavior, query traffic, several strategies and heuristics to improve query response time, etc. Typically, WSEs are composed of several services deployed in data centers, which must interact to get the best document results to user queries. Additionally, hardware specification like multithreading and network communications have to be taken into account. In this paper, we propose to model a servicebased WSE using the Discrete Event System Specification (DEVS) formalism, which is one of the most powerful methodologies for discrete event systems. We validate our proposed model against an actual MPI implementation of the WSE and a process oriented simulation. We evaluate the accuracy of the proposed model by evaluating metrics such as query throughput and we show that there is no relevant differences, just small fluctuations of less than 4%. © 2014 IEEE.